FCC algorithm for power loss diminution - Kanagasabai L. (Sumy State University, 2021)
In this work, the FCC algorithm has been applied to the power problem. Real power loss reduction, voltage deviation minimization, and voltage stability enhancement are the key objectives of the proposed work. The proposed FCC algorithm has been modeled based on the competition, communication among teams, and training procedure within the team. The solution has been created based on the team, players, coach, and substitution tactic. A preliminary solution of the problem is produced, and the initialization of the teams depends on the team’s formation with substitute tactics. Mainly fitness function for each solution is computed, and it plays an imperative role in the process of the algorithm. With the performance in the season, promotion and demotion of the teams will be there. Most excellently performed teams will be promoted to a senior division championship, and the most poorly performed team will be demoted to the top lower division league. Ideas and tactics sharing procedure, repositioning procedure, Substitution procedure, seasonal transmit procedure, Promotion and demotion procedure of a team which plays in the confederation cup has been imitated to solve the problem. Similar to an artificial neural network, a learning phase is also applied in the projected algorithm to improve the quality of the solution. Modernization procedure employed sequentially to identify the best solution. With and without voltage stability (L-index) FCC algorithm is evaluated in IEEE 30, bus system. Then the Proposed FCC algorithm has been evaluated in standard IEEE 14, 57,118,300 bus test systems without L-index. Power loss minimization and voltage stability index improvement have been achieved with voltage deviation minimization.